Estudo da imunoexpressão do reg-gamma e da beta catenina em queilites actínicas e carcinomas de células escamosas de lábio inferior - Parente, Patrícia Davin Gomes (2019)
Actinic cheilitis (QA) is a potentially malignant lesion that occurs mainly in men with light skin and a history of chronic sun exposure. Currently, it is not possible to predict which cases of QA will progress to Squamous Cell Carcinoma (SCC), so some biomolecular markers have been researched. Β-catenin is a multifunctional protein that is involved in cell-cell adhesion processes. The alteration of the cadherin-catenin complex has been demonstrated in SCC and correlated with tumor invasion, metastasis and worse prognosis of patients. REGγ is a proteasome activator that can promote the degradation of multiple proteins including p53 and MDM2. Studies show that REGγ is overexpressed in numerous cancers, suggesting that REGγ overexpression is involved in cancer progression. The aim of this study was to analyze the immunohistochemical expression of β-catenin and REGγ in cases of QA and lower lip squamous cell carcinoma (CCELI), comparing the immunohistochemical findings with the clinical and pathological data, in order to verify if there is any a correlation with tumor progression and whether they act synergistically in this process. Β-catenin and REGγ immunoexpression was analyzed semi-quantitatively in 30 cases of QA and 30 cases of CCELI according to the scores: 0 (no labeling); 1 (1-25% positive cells); 2 (26-50% positive cells); 3 (51-75% positive cells); 4 (> 75% positive cells). For statistical analysis, Mann-Whitney and Spearman tests were performed (p <0.05). Both QAs and CCELIs expressed the β-catenin protein, showing an increase in cytoplasmic and nuclear expression in cases of moderate and severe dysplasias. In CCELIs, membrane β-catenin immunoexpression was higher in cases of low grade malignancy. Both QAs and CCELIs expressed the REG-γ protein but no statistical significance between its expression and the degree of epithelial dysplasia was found, as well as between the immunoexpression of REG-γ and the clinicopathological parameters analyzed in the CCELIs. The results of the present study suggest that REG-γ overexpression and reduction in membrane expression of β-catenin may be important events in lip carcinogenesis. However, we believe that this protein is involved in the process of oral carcinogenesis. In this process, correlating the immunohistochemical expression of β-catenin with the expression of REG-γ, as we did not obtain statistically significant results, we suggest that β-catenin expression may not be directly influenced by the levels of REGγ expression.